Taxonomic review of the Miltochrista hollowai and M. curvifascia species-groups with descriptions of two new species from India (Erebidae: Arctiinae: Lithosiini) - Singh, Santosh; Kirti, Jagbir Singh; Joshi, Rahul; Singh, Navneet (Zootaxa, 2023)
The Miltochrista hollowai (Kirti & Gill, 2009) and M. curvifascia (Hampson, 1891) species-groups are reviewed, and two new species belonging to the M. hollowai species-group i.e., Miltochrista madathumala sp. nov. and M. kumarkaustubhi sp. nov. are described from South India. The female of M. paraarcuata is illustrated and diagnosed for the first time. Illustrations of adults and genitalia as well as diagnoses are provided for all the species considered.